Webs of reality : social perspectives on science and religion - Stahl, William A. (William Austin) (New Brunswick, N.J. Rutgers University Press, 2002)
An examination of the interrelationship between religion and science from a social science perspective, offering a broad view, and posing practical questions. The authors discover not only similarities between them but also a wide number of ways in which they complement each other.
Keywords: Religion and science -- Social aspects. Religion et sciences -- Aspect social. SOCIAL SCIENCE -- Sociology of Religion